Information exposure incentivizes consumers to pay a premium for emerging pro-environmental food: Evidence from China. (20th August 2022) - Li, Fuduo; Zhang, Kangjie; Yang, Peng; Jiao, Jian; Yin, Yanshu; Zhang, Yingnan; Yin, Changbin
Abstract: This study aims to reveal Chinese consumers' willingness to pay for Green manure-rice and its determinants by conducting an information intervention experiment. Results first showed that consumers' willingness to pay before and after the information intervention was 7.9 CNY/kg and 12.1CNY/kg, which was 2.6 CNY/kg and 6.8 CNY/kg premium than that of conventional rice, respectively. This finding highlights the necessity of eliminating information asymmetry in the pro-environmental food market through external information supply. Afterwards, the decision mechanism by which consumers pay for Green manure-rice was explored. The main conclusions are as follows. First, both subjective self-evaluation and environmental literacy had a positive and significant impact on consumer premium. This finding provides policymakers with the enlightenment that it is feasible to raise consumer premium by actively guiding their subjective self-evaluation and fostering their environmental literacy. Second, the moderating effect of information intervention on consumer awareness of Green manure-rice attributes was identified. This result not only emphasizes the positive role of food attribute labeling in guiding consumers' payment, but also further verifies the effectiveness of information strategy in promoting the development of Green manure-rice market. Third, information intervention narrowed the gap of payments between different consumer groups, which provides instrumental support for stabilizing the Green manure-rice market. These results are of great importance for both guiding the update of pro-environmental food market and promoting paddy agricultural system innovation in China. Graphical abstract: Image 1 Highlights: Information intervention experiment was used to reveal consumers' willingness to pay (WTP) for GMR and its determinants. Information exposure increased the premium for GMR from 2.6 CNY/kg to 6.8 CNY/kg. Subjective self-evaluation and environmental literacy have significant and positive effects on consumers' WTP. Information exposure can positively moderate the influence of consumers' awareness of GMR attributes on WTP. Information exposure narrowed the gap of payment amount between different consumer groups.